2013
DOI: 10.1007/s00394-013-0620-9
|View full text |Cite
|
Sign up to set email alerts
|

The α′ subunit of β-conglycinin and the A1–5 subunits of glycinin are not essential for many hypolipidemic actions of dietary soy proteins in rats

Abstract: Soy isoflavones were mainly responsible for the hypocholesterolemic effects and increased plasma free T3, whereas reduction in FFA, abdominal fat, liver weight and increased plasma total T3 were the effects of the soy proteins. Neither the α' subunit of β-conglycinin nor the A1-5 subunits of glycinin are essential for the hypolipidemic properties of soy proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Soy β-conglycinin was recently reported to modulate de novo lipogenesis by inhibiting hepatic fatty acid synthase mRNA expression and enzymatic activity, with concomitant decrease observed in the levels of hepatic lipids (triglycerides, TG; total cholesterol, TC; phospholipids, PL) and liver weight in OLEFT rats with non-alcoholic fatty liver disease [9]. Hypolipidemic activities have also been observed for squid homogenate [10], chicken protein extract [11], soy proteins [12] and fermented milk [13] in different dyslipidemic rat models. Moreover, a randomized controlled double-blind crossover trial with 68 human subjects demonstrated that feeding 25 g lupin protein (incorporated into rolls, bread, spread, sausage) per day for 28 days lowered plasma lipids (TG, TC, low-density lipoprotein [LDL] cholesterol); the effects were found to be more pronounced in subjects with severe hypercholesterolemia [14].…”
Section: Dietary Peptides and Hyperlipidemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Soy β-conglycinin was recently reported to modulate de novo lipogenesis by inhibiting hepatic fatty acid synthase mRNA expression and enzymatic activity, with concomitant decrease observed in the levels of hepatic lipids (triglycerides, TG; total cholesterol, TC; phospholipids, PL) and liver weight in OLEFT rats with non-alcoholic fatty liver disease [9]. Hypolipidemic activities have also been observed for squid homogenate [10], chicken protein extract [11], soy proteins [12] and fermented milk [13] in different dyslipidemic rat models. Moreover, a randomized controlled double-blind crossover trial with 68 human subjects demonstrated that feeding 25 g lupin protein (incorporated into rolls, bread, spread, sausage) per day for 28 days lowered plasma lipids (TG, TC, low-density lipoprotein [LDL] cholesterol); the effects were found to be more pronounced in subjects with severe hypercholesterolemia [14].…”
Section: Dietary Peptides and Hyperlipidemiamentioning
confidence: 99%
“…Moreover, a randomized controlled double-blind crossover trial with 68 human subjects demonstrated that feeding 25 g lupin protein (incorporated into rolls, bread, spread, sausage) per day for 28 days lowered plasma lipids (TG, TC, low-density lipoprotein [LDL] cholesterol); the effects were found to be more pronounced in subjects with severe hypercholesterolemia [14]. Although phytochemicals present in protein extracts can contribute to bioactivity, hypolipidemic effects (decrease in abdominal fat, liver weight and free fatty acids, FFA) have also been attributed to protein fractions [12]. There is no evidence of a direct interaction of native dietary proteins with physiological lipidome during dyslipidemia.…”
Section: Dietary Peptides and Hyperlipidemiamentioning
confidence: 99%
“…Sex-related differences were also observed in the initial study from which this project developed. Chen et al (2014) (White & Tchoukalova, 2013;Yang et al, 2012). The results from the present study indicate an increase in pparγ gene expression in female abdominal WAT in response to Harovinton hydrolysates.…”
Section: Glycinin/β-conglycinin α' Affects Pparγ Expression In a Sex-supporting
confidence: 58%
“…al., 2015). Further analysis of the soy peptides revealed that the α' subunit of β-conglycinin and the A1-5 glycinin subunits were not involved in the observed results (Chen, Wood, Gagnon, Cober, Frégeau-Reid, et al, 2014;Yamazaki et al, 2012). Therefore, a bioactive soy peptide involved in adipose tissue development remains to be identified.…”
Section: Recent Researchmentioning
confidence: 97%
See 1 more Smart Citation